Cyberterrorism and Enemy Criminal Law - Stuart Macdonald (Cyber War, 2015)
Governments are increasingly concerned with the threat of cyberterrorism. Many jurisdictions – including the UK, Australia, Canada and New Zealand – have expanded their statutory definitions of terrorism to also encompass cyberattacks which do not result in violence to people or property but which do seriously interfere with, or cause serious disruption to, electronic systems. The effect is to make available in such cases not only the full raft of terrorism-related investigative, procedural and sentencing provisions, but also all of the special pre-inchoate “precursor” terrorism offences. Whilst this may accord with these countries’ insistence that terrorism should be met with a criminal justice response, and that prosecution should be the preferred method of disrupting terrorist activity, it also poses challenges for theories of criminalisation.This chapter examines the UK's raft of precursor offences using the concept of enemy criminal law. Enemy criminal law is directed against a certain class of potentially dangerous offenders, imposing disproportionate sanctions and curtailing procedural rights in order to prevent future harm. The chapter warns of the danger that enemy criminal law may seep into and contaminate our ordinary criminal law. Moreover, enemy criminal law has the potential to undermine the moral authority and fairness of the criminal law, the very reasons why many common law jurisdictions insist on criminal justice responses to terrorism in the first place.